Chromosome-level genome assembly of the Adonis ladybird Hippodamia variegata - Hong-Ling Liu; Yan-Ping Yong; Xing-Long Wu; Zhi-Teng Chen; Shu-Jun Wei; Peng Cai; De-Qiang Pu (Scientific Data)
Abstract The Adonis ladybird (Hippodamia variegata), an important predator in agricultural ecosystems, plays a crucial role in biological control and is a significant model for evolutionary and genomic studies within Coccinellidae. Despite its ecological importance, the lack of a reference genome for H. variegata has limited in-depth investigations into its biology and potential as a biocontrol agent. Here, we present a high-quality, chromosome-level genome assembly of H. variegata. The final assembly spans 493.01 Mb, with a scaffold N50 of 28.19 Mb and a GC content of 36.41%. Hi-C sequencing data enabled the anchoring of 343.20 Mb to 10 chromosomes. Repetitive elements accounted for 258.56 Mb (52.44%) of the genome, with long interspersed nuclear elements (LINEs) being the most prevalent. We identified 37,348 protein-coding genes, of which 78.55% were functionally annotated in public protein databases. This high-quality genome assembly will serve as a valuable resource for furthering our understanding of Adonis ladybird’s evolutionary biology, enhancing its utility in pest management, and supporting future research on ladybird genomics.